Estimation of local magnitude from signal duration records of W.W. N. S. S. Shillong (MAUSAM, 1989)
Local magnitude (ML)in respect of 140 earthquakes, within magnitude spectra from 1.8. to 5.9, originating from within and around Shillong plateau in the northeast India, have been obtained from Wood. Anderson seismograms and corresponding signal duration in seconds have been determined from the earthquake records of short period vertical World Wide Network of Seismological Stations (WWNSS) seismograph at Shillong Observatory. Empirical equations have been obtained by the method of least squares for estimation of local magnitude, ML, from signal duration. It is seen that magnitude can be estimated within the limits of +-0.32 units. Empirical equations have also been obtained between, ML, and surface wave magnitude, Ms, of Rao and Nag (1981) and ML and signal duration magnitude, MD, of Dattatrayam and Srivastava (1988) The fitness of local magnitude, ML, as estimated from signal duration in the present study and also with Ms (Rao and Nag .1981):and MD (Dattatrayam and Srivastava 1988) is evaluated in terms of correlation coefficients and standard errors of estimates.